Pengaruh Dewan Komisaris, Dewan Direksi, Komite Audit dan Kepemilikan Institusional terhadap Pengungkapan Emisi Karbon - Dera Putri Amelya; Vinola Herawaty (Jurnal Pemimpin Bisnis Inovatif, 2026)
Carbon emission disclosure has become an important aspect of corporate sustainability reporting as stakeholders increasingly demand greater environmental transparency. This study aims to examine the influence of the board of commissioners, board of directors, institutional ownership, and audit committee on carbon emission disclosure in energy, industrial, and infrastructure companies listed on the Indonesia Stock Exchange during the 20212023 period. This research employed a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample was selected using purposive sampling, resulting in 366 firm-year observations. Data were analyzed using multiple linear regression with IBM SPSS. The results indicate that the board of commissioners and the board of directors do not have a significant effect on carbon emission disclosure. Institutional ownership has a positive and significant effect, indicating that institutional investors encourage greater environmental transparency. Meanwhile, the audit committee has a significant but negative effect, suggesting that its supervisory role remains primarily focused on financial reporting rather than environmental disclosure. Overall, the findings imply that corporate governance mechanisms have not fully enhanced carbon emission disclosure, except through the monitoring role of institutional ownership. This study contributes to the literature on corporate governance and environmental disclosure and provides practical implications for companies and investors in improving sustainability reporting practices.